2023
DOI: 10.3389/fpsyt.2023.1114907
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of robot-based to human-based intervention in improving joint attention in autistic children

Abstract: BackgroundChildren with autism have impairments in initiation of joint attention (IJA) and response to joint attention (RJA).AimsThe present study compared the learning effectiveness of robot-based intervention (RBI) with that of content-matched human-based intervention (HBI) in improving joint attention (JA). We examined whether RBI would enhance RJA, in comparison to HBI. We also examined whether RBI would increase IJA, in comparison to HBI.Methods and proceduresThirty-eight Chinese-speaking children with au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Two other studies carried out, respectively, with a CuDDler bear robot and a CommU robot also demonstrated improvement in this behavior in children aged 4-5 and 5-6 years [38,39]. Joint attention training with robots (HUMANE) is more effective than training with humans in improving response and initiation of joint attention in 6-9-year-old children with ASD [40]. In a gaze cueing paradigm, adults with ASD followed the gaze of an EDDIE robot more than that of a human [43].…”
Section: Fostering Communication and Social Interactionmentioning
confidence: 81%
See 1 more Smart Citation
“…Two other studies carried out, respectively, with a CuDDler bear robot and a CommU robot also demonstrated improvement in this behavior in children aged 4-5 and 5-6 years [38,39]. Joint attention training with robots (HUMANE) is more effective than training with humans in improving response and initiation of joint attention in 6-9-year-old children with ASD [40]. In a gaze cueing paradigm, adults with ASD followed the gaze of an EDDIE robot more than that of a human [43].…”
Section: Fostering Communication and Social Interactionmentioning
confidence: 81%
“…The same question can be asked about the generalization of these behaviors to human partners once the sessions with the robot are over: the abilities acquired with the robot then seem to be transferable to human-human interactions [19,21,38,52,65]. The children would be able to apply the skills acquired with the robot in new contexts, at least for joint attention [39,40], gesture imitation [65], and emotion recognition [21]. Parents of children with ASD who underwent a month of training with the robot around social games reported significant changes in their child's social behavior: increased eye contact, interaction initiation, and response to communicative acts [19].…”
Section: Methodological Limitationsmentioning
confidence: 99%